Implementation of Lesson Study in Supporting the Values of Tudang Sipulung as a Local Culture in ESP Classroom - Muhammad Hasby; Muthmainnah Muthmainnah (Universitas Cokroaminoto Palopo, 2019)
Lesson Study was firstly applied in Palopo City (Indonesia), and Universitas Cokroaminoto Palopo was the only institution, which is entrusted to develop it outside Makassar, as the learning process in 2013 until the present time. The models of cooperative and collaborative learning have indicated the positive thing in improving the material of English for Specific Purposes and reduce the impractical theory-based course, the activities of lesson study are generally run properly and it needs the well-managed scheduled to arrange all the necessary things in it from early to the last cycle of the lesson study. In short, the lesson study is improving the students’ cooperation, collaboration motivation, and initiative in learning ESP course. The sharing and discussion among the lecturers before and after the class is also revitalizing the spirit of traditional local wisdom and values, which is called tudang sipulung, it is clearly seen that the cooperation, collaborative, mutual respects spirit in lesson study is relevant to the local wisdom and supports the local values of tudang sipulung.